청소년이 지각한 부모 양육태도 잠재유형에 따른 행복감 차이 - 김시아; Kim Si Ah; 주영하; Ju Young Ha (청소년복지연구, 2025)
본 연구는 부모의 양육태도에 따라 청소년의 행복감 수준이 어떻게 달라지는지를 분석하고자 하였다. 이를 위해 한국청소년정책연구원의 「한국아동·청소년패널조사 2018(KCYPS 2018)」 초4 패널 6차년도(2023) 데이터를 활용하였으며, 중학교 3학년 청소년 2,240명의 자료를 최종분석에 포함하였다. 부모 양육태도는 따뜻함, 자율성 지지, 구조제공, 거부, 강요, 비일관성 등 여섯 요인으로 구성되었으며, 이를 바탕으로 잠재프로파일분석(latent profile analysis)을 실시한 결과 ‘이상지향적 양육형’, ‘이상적 양육형’, ‘강한 비일관적 양육형’, ‘방임형’, ‘비일관적 양육형’의 5가지 유형이 도출되었다. 이후 각 유형 간 행복감 수준의 차이를 검증한 결과, ‘이상적 양육형’의 행복감이 가장 높았으며, ‘강한 비일관적 양육형’, ‘이상지향적 양육형’, ‘방임형’이 그 뒤를 이었고, ‘비일관적 양육형’은 가장 낮은 행복감을 나타냈다. 이러한 결과는 청소년의 행복감이 부모의 정서적 반응성과 양육의 일관성에 따라 유의하게 달라질 수 있음을 시사한다. 본 연구는 부모 양육태도의 유형화와 청소년의 정서적 특성 간 관계를 실증적으로 검토하였다는 점에서 의의를 가지며, 향후 청소년의 정서적 안녕을 증진하기 위한 부모교육 프로그램 개발 및 가족지원 정책 개발 방향을 제안하였다. This study examined how adolescents’ happiness varies according to their perceived parenting styles. Data were drawn from the sixth wave (2023) of the Korean Children and Youth Panel Survey 2018 (KCYPS 2018), focusing on 2,240 third-grade middle school students. Parenting style was measured across six dimensions: warmth, autonomy support, structure, rejection, coercion, and inconsistency. Latent profile analysis identified five parenting style profiles: ideal-oriented, ideal, strongly inconsistent, neglect, and inconsistent. Differences in happiness across these groups revealed that adolescents in the “ideal” profiles reported the highest levels of happiness, followed by the “strongly inconsistent” and “ideal-oriented”, “neglect” groups. The “inconsistent” group showed the lowest happiness levels. These findings suggest that adolescents’ happiness is significantly influenced by parental emotional responsiveness and behavioral consistency. By identifying heterogeneous parenting profiles and linking them to adolescent well-being, this study contributes empirical evidence to the literature on family dynamics and youth mental health. This study is significant in that it empirically examined the relationship between typologies of parenting styles and adolescents’ emotional characteristics. Building on these findings, it proposes directions for developing parenting education programs and family support policies to enhance adolescents’ emotional well-being.